2016
DOI: 10.1016/j.chemosphere.2016.07.098
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of emerging contaminants in sewage sludge after anaerobic digestion

Abstract: Nowadays, there is an increasing concern over the presence of contaminants in the aquatic environment, where they can be introduced from wastewater after their incomplete removal in the treatment plants. In this work, degradation of selected emerging pollutants in the aqueous and solid phases of sewage sludge has been investigated after anaerobic digestion using two different digesters: mesophilic and thermophilic. Initially, sludge samples were screened by ultra-high-performance liquid chromatography coupled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 41 publications
5
25
0
1
Order By: Relevance
“…Even valsartan, with a maximum EWW concentration of more than 23,000 ng/L, has only been detected in one GW sample with a concentration of 9.5 ng/L. This low rate of detection is due to the fact that this compound can transform into its TP [63] and, to a small extent, to be retained in the vadose zone, which in this case has an average depth of 20 m.…”
Section: Suggested Coes As Indicators Of Reclaimed Water Arrival In Dmentioning
confidence: 88%
See 2 more Smart Citations
“…Even valsartan, with a maximum EWW concentration of more than 23,000 ng/L, has only been detected in one GW sample with a concentration of 9.5 ng/L. This low rate of detection is due to the fact that this compound can transform into its TP [63] and, to a small extent, to be retained in the vadose zone, which in this case has an average depth of 20 m.…”
Section: Suggested Coes As Indicators Of Reclaimed Water Arrival In Dmentioning
confidence: 88%
“…Several studies have revealed that this compound is considered to be highly stable in water/sediment [59], and, therefore, its presence in GW has been reported by a number of researchers [17,[60][61][62]. Concerning venlafaxine, recent studies have indicated that it is not a compound that degrades easily and rapidly into its TP [63]. Therefore, this behavior might help to preserve the compound in the EWW during the process of irrigation and subsequent storage in the aquifer saturated zone.…”
Section: Assessment Of the Occurrence Spatial Distribution And Concmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Gago-Ferrero et al [34] achieved LOQs of 4.1 ng/g for diclofenac and 9.8 ng/g for salicylic acid by applying a method based on UAE and UHPLC-MS/MS. In contrast, Boix et al [38] reported lower limits (eg., 63 ng/g for diclofenac and ng/g for salicylic acid) using a similar method but with HPLC as the chromatographic stage. Regardless of these factors, through the use of quantification approaches such as internal standard with isotope dilution, standard addition or matrix-matched techniques most technical deficiencies during extraction, clean-up, instrumental analysis, etc.…”
Section: Accepted Manuscriptmentioning
confidence: 92%
“…Because of a large number of emerging organic contaminants there is a need for future monitoring programmes and technological changes in sewage sludge management in order to reduce the concentration of organic contaminants to a level acceptable for sewage sludge application [27].…”
Section: Introductionmentioning
confidence: 99%